Circular Inventory Management Practices and Environmental Performance of Food and Beverage Manufacturing Firms in Kenya - Kunni, Elle Guyatu; Nyile, Erastus (International Journal of Supply Chain and Logistics, 2026)
Purpose: The purpose of this study was to examine how shelf-life extension and lean stock holding affected the environmental performance of food and beverage manufacturing firms in Kenya. Grounded in circular economy principles, the study focused on reducing waste associated with overproduction and product spoilage. It sought to provide evidence on how improved inventory practices enhanced sustainability and minimized environmental degradation in the sector. Methodology: The study adopted a descriptive research design to enable systematic data collection and analysis. The target population comprised 329 food and beverage manufacturing firms listed by the Kenya Association of Manufacturers, from which a sample of 181 firms was selected using Yamane’s formula and simple random sampling. Primary data were collected using structured questionnaires administered to supply chain managers. Data were analyzed using both descriptive and inferential statistics, including correlation and regression analysis. Findings: The findings revealed that both shelf-life extension and lean stock holding have significant positive effects on environmental performance. Shelf-life extension practices such as cold chain management and inventory rotation were found to reduce product spoilage and waste, thereby improving resource efficiency. Lean stock holding practices minimized excess inventory, reduced overproduction, and lowered environmental impacts associated with storage and disposal. Inferential results confirmed that both variables are statistically significant predictors of environmental performance. Unique Contribution to Theory, Policy and Practice: This study contributes to theory, policy, and practice by demonstrating how specific inventory management practices enhance environmental performance in manufacturing contexts. Practically, it shows that food and beverage firms can improve sustainability by investing in efficient cold chain systems, strengthening demand forecasting, and adopting lean practices such as Just-in-Time to reduce waste and optimize resources. Theoretically, it provides empirical evidence on the role of shelf-life extension and lean stock holding within circular economy frameworks.